ANALISA FAKTOR-FAKTOR KEPUASAN MITRA KERJA SAMA PADA PROGRAM DOKTOR ILMU EKONOMI UNIVERSITAS TRISAKTI - Ekasari, Ayu; Usman, Bahtiar; Warsindah, Lucy (Premium Insurance Business Journal, 2022)
This study aims to analyze the factors that determine the satisfaction of partners in Doctoral Programs in Economics, Universitas Trisakti. The population of this study consists of thirty-six institutions/groups that have been actively involved in some activities with the Doctoral Programs in Economics, Universitas Trisakti. The data collection method is a survey by distributing questionnaires to all members of the population. The data is analyzed using the mean score taken from the results of statistic descriptive. Results show that on average the partners are satisfied with the cooperation that has been established. The contribution of this research is to provide inputs for the Doctoral Programs in Economics, Universitas Trisakti. in maintaining and improving factors that influence partners' satisfaction. From an academic perspective, this research expands the domain of relationship marketing which has been dominated by customer satisfaction. The weakness of this research is the use of descriptive statistics. Future research can explore other factors that influence partner satisfaction and use importance-performance analysis to analyze the data.